Supporting Women and Children Returning from Violent Extremist Contexts: Proposing a 5R Framework to Inform Program and Policy Development - Ellis, B. Heidi; King, Michael; Cardeli, Emma; Christopher, Enryka; Davis, Seetha; Yohannes, Sewit; Bunn, Mary; McCoy, John; Weine, Stevan (Terrorism and political violence, 2024)
Women and children returning from areas formerly controlled by the Islamic State typically have experienced high levels of trauma and indoctrination, further complicating politically fraught efforts at reintegration and resettlement. Consequently, countries around the world are grappling with how best to manage the return of these women and children. To help better understand which types of programming can contribute to the successful, non-violent reintegration of these individuals, we incorporated ideas from existing Repatriation and Rehabilitation (R&R) literature, field practitioners, R&R subject matter experts, and literature from adjacent fields (e.g., refugee resettlement, criminal justice, psychological resilience) into a recommended best practice approach to supporting returning women and children. We propose a shift from "R&R" programming to what we call the "5R" framework: Repatriation/Resettlement, Reintegration, Rehabilitation, and Resilience. This shift provides conceptual clarity related to how different program elements target proximal goals (e.g., wellbeing and personal safety, belonging and opportunity, non-violence, and dignity), and how programming can shift from more centrally- and government-held services to informal and community-based supports.